Evaluation of HFMI in welded cover-plates for strengthening of steel bridges - A review of previous research and Finite Element Analysis based on Effective Notch Stress method to evaluate HFMI’s applicability on steel bridges - Engdahl, Amilia; Khoulani, Noora (My University, 2023)
Europe had an expansion in infrastructure during the 20th century, which led to the construction of a large number of bridges. The majority of bridges in service today are over 50 years old, meaning that they have either surpassed or are approaching their expected service life span. Additionally, due to increased traffic and traffic loads, old bridges are burdened significantly more than what they were originally designed for. A common way to reinforce steel beam bridges is by adding cover plates to the bottom flange. Currently, these cover plates are connected using bolts. This is because the more attractive welding method contributes to poor fatigue performance, resulting in shorter bridge service lives. Hence, post-weld treatment techniques are being studied as a possible solution to fatigue-related issues in welded details. High-frequency mechanical impact (HFMI) is one of today’s most promising methods. However, there is a lack of research on HFMI-treated cover-plates fatigue performance. But this is currently an area of interest. Therefore, this master’s thesis assesses whether HFMI-treated cover plates are a viable solution for strengthening steel bridges. The research was conducted by reviewing and re-analysing previous studies on HFMI-treated cover-plated structures. This was done by performing Finite Element analyses in Abaqus. Maximum principal stresses were obtained at weld toe and root to perform fatigue assessment according to the Effective Notch Stress method. Additionally, the stress behaviour of different cover-plated structures was examined and compared. Finally, the cover-plates have been modified to expand the study. The study concluded that HFMI-treatment is an effective solution to increase fatigue performance of welded cover-plated structures subjected to bending. Furthermore, it was found that treated cover-plates have the potential to provide fatigue strength comparable to, or even exceeding, bolted ones. It was also concluded that, unlike as-welded and axially loaded cover-plates, the most likely failure location for HFMI treated cover-plates subjected to bending is at the weld root. A solution to increase the fatigue strength of the weld root was investigated in this study. It was shown that changing the root position results in additional improvement in the fatigue strength of treated cover-plates.
Keywords: Cover-plates, HFMI, UIT, Effective Notch Stress method, Weld, S-N curve, Fatigue, Cover-plates in bending, bridges, Finite Element analysis, Abaqus